2014
DOI: 10.3982/qe170
|View full text |Cite
|
Sign up to set email alerts
|

Partial identification of finite mixtures in econometric models

Abstract: We consider partial identification of finite mixture models in the presence of an observable source of variation in the mixture weights that leaves component distributions unchanged, as is the case in large classes of econometric models. We first show that when the number J of component distributions is known a priori, the family of mixture models compatible with the data is a subset of a J(J − 1)dimensional space. When the outcome variable is continuous, this subset is defined by linear constraints, which we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
86
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(86 citation statements)
references
References 31 publications
0
86
0
Order By: Relevance
“…1 Assumption 1 (Mixture with exclusion). F(y|x) ≡ P(Y ≤ y|X = x) decomposes as the two-component mixture The assumption that the component distributions do not depend on X embodies our exclusion restriction; see also Henry et al (2014).…”
Section: Mixtures With Exclusion and Tail Restrictionsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 Assumption 1 (Mixture with exclusion). F(y|x) ≡ P(Y ≤ y|X = x) decomposes as the two-component mixture The assumption that the component distributions do not depend on X embodies our exclusion restriction; see also Henry et al (2014).…”
Section: Mixtures With Exclusion and Tail Restrictionsmentioning
confidence: 99%
“…The exclusion restriction is also implied by the conditional-independence restriction that underlies the results of Hall and Zhou (2003) and others on multivariate mixtures. Henry et al (2014) have shown that our exclusion restriction implies that both the mixing proportions and the component distributions lie in a nontrivial set. However, they only proved partial identification, and they did not discuss inference.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their approach can be applied to a more general class of latent structures that feature some form of conditional independence, such as hidden Markov models with finite state spaces (see Petrie [1969] for seminal work on this) and to random-graph models. We note that, although the availability of two measurements can suffice in problems featuring additive structures, the work of Henry, Kitamura and Salanié [2013] shows that two measurements will only deliver set-identification of parameters in more general latent-structure models. Li and Vuong [1998], Bordes, Mottelet and Vandekerkhove [2006], and Gassiat and Rousseau [2013], among others, present results for additive models.…”
mentioning
confidence: 99%